EVALUASI DAMPAK BANJIR AKIBAT PERUBAHAN ALUR SUNGAI CITANDUY HULU DI DESA TANJUNGKERTA, TASIKMALAYA-JAWA BARAT - Maulana, Ari Azhar; Rosalina, Harnita (JURNAL SUMBER DAYA AIR, 2022)
Since 1996 there have been frequent floods in the upstream area of the Citanduy River, especially during the rainy season. The flood also inundated part area of the Suryalaya Islamic Boarding School located in Tanjungkerta Village, Pagerageung District, Kabupaten Tasikmalaya. In this case, the community took the initiative with self-subsident activities to reduce the impact of flood by diverting the Citanduy River channel without any communication with river authority. This analysis purposed to evaluate the cross-section capacity due to narrowing the upper Citanduy River. Hydrological analysis was initiated to determine the characteristics of catchment area in study area. 1D and 2D hydraulic analysis using HEC-RAS application with unsteady flow analysis to determine water level, flood distribution, and river flow velocity. Using the annual Q25 plan discharge taking into existing capacity and geometric characteristics. Validation of modeling results by observing directly the water level at locations that affected by flooding condition due to high rainfall intensity. Conclusions are based on the results of hydraulic hydrological analysis applied to the research object. Shortening of river channel due to siltation causes a decrease in the area of the river channel in bank conditions. Actually condition of the Citanduy River after draining discharge over a 2-year return period, there was a flood in the river cross-section of Sta. 400 – 1035 rivers overflow with variations in depth of ±40 – 80 cm when model with a discharge period of 25-years.  The recommendation for further research is to assess the river capacity to analyze erosion and sedimentation that occurs in the watershed. Conducting a more comprehensive study, involving the three core components, that is Hydraulics, Ecology, and Morphology, so that proposed alternative solutions have a good impact on all aspects, not only solving one problem but causing other problems.Keywords : Flood modeling, river shortcut, Upper Citanduy River